Congress off the record : the candid analyses of seven members - Bibby, John F.; American Enterprise Institute for Public Policy Research (Washington : American Enterprise Institute, 1983)
The roundtable discussions have been reviewed, edited, and arranged by topic in the pages that follow.
"Roundtable participants: seven members of the Class of 1978 United States House of Representatives; William J. Baroody, Jr., president, American Enterprise Institute; Congress Project staff members, American Enterprise Institute, Michael J. Malbin, Thomas E. Mann, Norman J. Ornstein."
osc 08/04/2019
Loans